THE EFFECT OF RELAXATION MUSIC ON PAIN LEVELS IN THE FIRST STAGE OF ACTIVE LABOR AT THE KARTIKA HUSADA CLINIC - Diyah Sulistyawati; Rosyidah Alfitri (Yayasan Nuraini Ibrahim Mandiri, 2026)
Labor pain in the active phase of the first stage of labor is a physiological condition caused by uterine contractions and cervical dilation, which may lead to discomfort and increased maternal anxiety. One non-pharmacological intervention that can be used to reduce labor pain is relaxation music therapy using the sound of trickling water, which has a calming effect. This study aimed to determine the effect of trickling water music therapy on reducing pain levels during the active phase of the first stage of labor. This study employed a quantitative method with a quasi-experimental design using a Posttest-Only Control Group Design approach. The sample consisted of 30 mothers in the active phase of the first stage of labor, divided into an intervention group (n = 15) and a control group (n = 15), selected through purposive sampling. Pain intensity was measured once after the intervention using the Numeric Rating Scale (NRS). The intervention group received trickling water music therapy, while the control group received standard care. The results showed that pain levels in the intervention group were lower than those in the control group. Statistical analysis using the Mann-Whitney U Test revealed a significant difference between the two groups (U = 6.000; Z = -4.491; p < 0.001). The intervention group had a lower mean rank (8.40) compared to the control group (22.60), indicating lower pain intensity following the intervention. The study concludes that trickling water music therapy is effective in reducing labor pain during the active phase of the first stage of labor.